Effect of solvents and temperature on the structural, thermodynamic and electronic properties of capped phenylalanine: A computational study (Journal of Bangladesh Academy of Sciences, 2022)
Effects of solvents and temperature on the structural, thermodynamic, and electronic properties of L-configuration of N-acetyl-phenylalaninyl amide (NAPA) were studied using density functional theory (DFT) and time-dependent density functional theory (TD-DFT) approach. Enthalpy (H), entropy (S) and specific heat capacity (Cv) were found to increase with the increase of temperature (100 K-1600 K) because of the increasing intensities of molecular vibration. On the contrary, Gibb’s free energy (G) was found to decrease with the increase of temperature. The UV-light absorption maximum, λmax, is red-shifted in the presence of polar protic, aprotic and non-polar solvents. On the other hand, calculation shows that dipole moment in polar solvents (protic and aprotic), non-polar solvents, and the gas phase are ~3.35, ~3.0, and 2.5 D, respectively. However, no significant change was found in the HOMO-LUMO energy gap in the presence of different types of solvents.J. Bangladesh Acad. Sci. 45(2); 205-215: December 2021